INNOVATION IN ART EDUCATION THROUGH ADAPTIVE AND DIGITAL LEARNING PLATFORMS - Aswitha V; Shalini E; Rajashri CK; Snehaa G; Packirisamy, Subbulakshmi; Ogeri, Doris Ifeoma (ShodhKosh: Journal of Visual and Performing Arts, 2026)
The use of digital tools and adaptive learning systems has changed the modern art education greatly by making it flexible, personalized, and interactive. Conventional in person training is usually constrained in terms of accessibility, personal feedback and resources. Adaptive digital learning systems solve these issues by means of applying artificial intelligence and data analytics and interactive multimedia tools to customize learning material and content based on artistic talents, learning speeds, and creativity that the students have. This paper discusses the theoretical and technological underpinnings of adaptive online platforms in art education as well as its educational implications. It investigates the use of virtual studios, digital drawing instruments, augmented reality (AR), virtual reality (VR), and collaborative multimedia space in improving artistic experimentation and creativity. The study also examines the algorithms of personalization, AI-informed feedback, and adaptive evaluation models that facilitate the process of unceasing enhancement of artistic learning outcomes. Findings suggest that adaptive online platforms can equally contribute to creativity and engagement in addition to increasing accessibility to a wide range of learners through flexible learning opportunities and inclusive learning materials.